The use of organ donor blood in liver transplantation. Issue 9 (16th September 2021) - Tang, Gia Toan; Shaylor, Ruth; Hui, Victor; Przybylowski, Greg; Jones, Robert McLaren; Starkey, Graham; Perini, Marcos Vinicius; Wang, Bao‐Zhong; Zantomio, Daniela; Hogan, Chris; Fink, Michael Anthony
Abstract: Background: Blood removed from organs during deceased donor organ procurement is routinely discarded but is a potential resource for donor‐specific transfusion (DST) in subsequent liver transplantation (LT). This study retrospectively analyses the impact of DST on intraoperative bank blood product usage, long‐term graft, and patient survival, as well as frequency of rejection post‐LT. Methods: A total of 992 adult LT performed from 1993 to 2018 in a single quaternary center were included. Intraoperative blood product usage, patient, and graft survival, as well as acute and chronic rejection were assessed in patients who received blood retrieved from the organ donor, the "donor blood" (DB) group ( n  = 437) and patients who did not, the "no donor blood" (NDB) group ( n  = 555). Results: Processing of DB ensured safe levels of potassium, magnesium, and insulin. There were fewer units of bank red blood cells transfusion required in the DB group compared to NDB group (2 vs. 4 units, P  = .01). Graft survival was significantly superior in the DB group (10‐year survival 75% vs. 69%, respectively, P  = .04) but DST was not an independent predictor of graft survival. There was no significant difference in patient survival or rejection between the groups. There was no difference in treated, biopsy‐proven rejection between the two groups. Conclusions: This is the first large‐cohort study assessing long‐term outcomes of intraoperative DST in LT. The collection of organ donor blood and subsequent use in LT recipients appeared feasible with appropriate quality checks ensuring safety. DST resulted in a reduction in the use of packed red blood cells. There was no difference in the rate of rejection or graft or patient survival.